Strategi Digital Public Relation dalam Sosialisasi Program UMKM Juara di Dinas Koperasi dan Usaha Kecil (DISKUK) Provinsi Jawa Barat - Mutia Salsabila; Rahmat Wisudawanto; Esfandani Peni Indreswari (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This UMKM juara program targets participants from entrepreneurs in West Java who are willing to commit to progress and development in the business sector. UMKM will move up a class and utilize technology in business, especially information technology for a wider market. Therefore, a digital public relations publication strategy is needed to produce messages that are easy to understand and effective in delivery to the public. This study aims to analyze the digital public relations strategy in the socialization of the UMKM juara program at the West Java Provincial Cooperative and Small Business Service (DISKUK). This study is a qualitative study using primary data sources, namely the DISKUK JABAR public relations staff. The Instagram account and DISKUK JABAR technical guidelines are secondary data sources. The primary data are the results of interviews with the DISKUK JABAR public relations department. Secondary data is the uploads from the DISKUK JABAR Instagram account. This study used a digital public relations strategy from Holtz (2009) which includes the goals, strategy, objectives, and tactics. The results of the study show that DISKUK JABAR has implemented a digital public relations strategy. The SWOT results show that the stages of the digital public relations strategy have been implemented. Meanwhile, the digital public relations strategy that is still lacking is the strategy and objective stage. This is due to the lack of socialization in activities regarding the accompanying curriculum and the limited human resources in monitoring and evaluation assistance. Therefore, it can cause the implementation of the UMKM Juara program to be less effective